Introduction to the NCAA men`s basketball prediction methods issue - Glickman, M. E.; Sonas, J. (Journal of Quantitative Analysis in Sports, 2015)
We are delighted to present a special collection of articles in this issue of the Journal of Quantitative Analysis in Sports (JQAS) on predicting game outcomes in the NCAA men`s basketball tournament, more commonly known as "March Madness." The NCAA tournament is a single elimination knockout event that begins with 64 teams after four teams have been eliminated through a play-in round a few days before the tournament begins. The idea for this special series of papers arose from a prediction competition we hosted on the Kaggle website (along with Will Cukierski of Kaggle and Ed Feng of The Power Rank) in which contestants were required to predict the results of the 2014 NCAA men`s basketball tournament. The competition was sponsored by Intel and came with a $15,000 cash prize for the first-place finisher. It became evident from Kaggle forum discussions hat some contestants were developing innovative analytical approaches for making predictions. We felt that inviting submissions for JQAS based on these innovative methods would lead to a fascinating set of articles. The culmination of this process is on display in the current JQAS issue.